Performance Enhancementof Hybrid Solar Pv Module By A Novel Configurations - et. al., Angham Fadil Abed, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In common, energy input to PV panels is the incident radiation which is converted to electrical energy to external load as energy output. Percentage of 4–17% of the incident solar radiation only converts to electric power by PV module. So, more than 50% of the solar energy converts into heat inside panels and this increased the temperature of PV module. Decrement of electricity efficiency and power with a continuous structural deterioration of modules is due to long thermal stress period as a result from increasing PV module temperature. In order to get better efficiency of PV module and to reduce its thermal degradation rate, there is an effective method of reducing its temperature of operating through utilizing of PV module cooling technique. In the present study, experimental system was designed in an effective and simple way in construction. Outdoor testing conditions were carried for produce distilled water from cooling PV module by using a wetted porous cotton wick structure. The proposed module is assumed to represent an integration of solar still with a PV(PV/T) .Total efficiency and productivity of proposed module was enhanced as seen from results. Results of experimentations showed that the maximum instantaneous PV electrical efficiency acquire the highest value of about (14.4%) through desalination with back wick (PVWDWBW) compare to 13.9% for (PVWD) that indicate an improvement of about (2%) as compare to PV module without system of cooling(PV only). The daily (PVWDWBW) thermal efficiency (ηd) is about (21.4 %) as compared to (18.4%) for(PVWD). For productivity, temperatures, and different terms, results were presented. For productivity, temperatures, and different terms, results were presented.